BELAJAR DARI RUMAH PADA MASA PANDEMI COVID 19 - anastasia - Heni; Clara Ajisuksmo (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2022)
Teachers, students and parents have an important role in learning from home during the COVID-19 Pandemic. This study aims to determine the role of teachers, students, parents and schools in implementing the so-called learning from home pandemic policy. Positive and negative experiences including opportunities and challenges by the pandemic COVID-19 situation can be reflected and become recommendated for the implementation of learning process and sustainability. This research was conducted by using a mix-method. The quantitative method is carried out by survey based on using google form. While, the qualitatif method conducted based on interviews with students, techers, parents and schoolsâ€™ principals. The conclusion of this research states that the COVID-19 pandemic is en emergencys (dangerous) situation that must be handled by seeking alternative of creative learning process to bring valuable experience for Â schools in cope with severe suffering while firmly growing and sustaining the spirit towards maturity.